Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00430-014-0383-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural and semisynthetic diterpenoids with antiviral and immunomodulatory activities block the ERK signaling pathway

Abstract: The pathogenesis of many viral infections lies on the damage caused by the immune response against the virus. Current antiviral drugs do not act on the inflammatory component of the disease. Thus, new compounds that inhibit both viral multiplication and the immunopathology elicited by the virus are an approach that should be considered. In the present study, we identified two jatropholones (2A and 5B) and one carnosic acid derivative (9C) that significantly inhibited multiplication of TK+ and TK- strains of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
(60 reference statements)
4
14
0
Order By: Relevance
“…Then, J774A.1 cells were transfected with the NF-jB-LUC reporter vector and, 24 h later, infected with HSV-1 and treated with b-escin (5 lg/ml) and AH (20 lg/ml) for 8 h. We found that b-escin and AH did not induce NF-jB and AP-1 activation in uninfected cells. We verified that HSV-1 induced a strong NF-jB and AP-1 activation as previously reported, [9] and that, interestingly, both pathways were strongly inhibited by b-escin and AH in HSV-1 in J774A.1 HSV-1-infected cells (Figure 5a). We next determined whether the NF-jB and AP-1 pathways were affected by b-escin (5 lg/ml) and AH (20 lg/ml) in macrophages stimulated with different TLRs ligands during 8 h. Stimulation with TLRs ligands activated NF-jB and AP-1 pathways, whereas b-escin and AH prevented TLRs induced NF-jB and AP-1 activation (Figure 6a).…”
Section: Nf-jb and Ap-1 Activation Is Inhibited By B-escin And Ah Aftsupporting
confidence: 91%
See 2 more Smart Citations
“…Then, J774A.1 cells were transfected with the NF-jB-LUC reporter vector and, 24 h later, infected with HSV-1 and treated with b-escin (5 lg/ml) and AH (20 lg/ml) for 8 h. We found that b-escin and AH did not induce NF-jB and AP-1 activation in uninfected cells. We verified that HSV-1 induced a strong NF-jB and AP-1 activation as previously reported, [9] and that, interestingly, both pathways were strongly inhibited by b-escin and AH in HSV-1 in J774A.1 HSV-1-infected cells (Figure 5a). We next determined whether the NF-jB and AP-1 pathways were affected by b-escin (5 lg/ml) and AH (20 lg/ml) in macrophages stimulated with different TLRs ligands during 8 h. Stimulation with TLRs ligands activated NF-jB and AP-1 pathways, whereas b-escin and AH prevented TLRs induced NF-jB and AP-1 activation (Figure 6a).…”
Section: Nf-jb and Ap-1 Activation Is Inhibited By B-escin And Ah Aftsupporting
confidence: 91%
“…Thus, considering the rise of the resistant viruses against the current antivirals and the adverse effect of corticoids, there is a need to search for new potential anti‐HSV agents that act with different mechanisms. In this sense, the finding of novel compounds that inhibit both viral multiplication and the immunopathology triggered by the virus is an interesting approach that is being considered …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of TLR stimulation on RSV infection, HEp-2 and A549 cells were infected with RSV A2 (moi = 1) and treated with different concentrations of Pam2CSK4 (TLR 2/6 agonist), poly(I:C)-HMW (TLR 3 agonist), LPS (TLR 4 agonist), imiquimod (IMQ, TLR 7 agonist), resiquimod (RSQ, TLR 7/8 agonist) or CpG ODN 2395 (TLR 9 agonist). These TLR agonists concentrations were chosen based on published data that demonstrate TLR stimulation in different cell types in vitro (Tissari et al, 2005;Kan et al, 2012;Bueno et al, 2015;Lucifora et al, 2018;Salinas et al, 2019). After 24 h, the amounts of infectious virus particles in the culture medium were decreased only by treatment with imiquimod, while the other TLR agonists did not affect viral replication at these concentrations tested (Fig.…”
Section: Evaluation Of the Anti-rsv Effect Of Tlr Agonists In Vitromentioning
confidence: 99%
“…The jatrophane and lathyrane diterpenoids are unique classes of macrocyclic systems featuring a trans-bicyclo [10.3.0]pentadecane framework, typically including hydroxylated or other oxygenated substituents. Such natural products have demonstrated a wide variety of biological properties including P-glycoprotein modulation 7 and antiproliferative, 8 antimalarial, 9a anti-inflammatory, 10 and antiviral properties. 11 The main objective of the present work was to identify novel natural products as potential sources of anticancer agents, particularly for the treatment of drug-resistant cancers.…”
mentioning
confidence: 99%